Epidemiological features of COVID-19 family outbreaks in children (One Health & Risk Management, 2021)
Introduction. The population of all ages is susceptible to SARS-CoV-2 virus. It is important to determine the role of the child in COVID-19 cases maintenance and spreading. Some research showed that most COVID-19 cases in children were associated with their families.Material and methods. The descriptive study is carried out on the basis of family outbreaks epidemiological peculiarities evaluation, concerning the age of the children, the onset of the disease, communities living environment. The research group included 160 family outbreaks, which required hospitalization at MCHCDC PMSI, between January and February 2021.Results. The number of family outbreaks increased (n=88 versus n=72) in February versus January 2021. The rate of outbreaks in schoolchildren increased from 37.5% in January to 53.4% ​​in February. The onset of the disease in the outbreaks varies depending on the age category of the involved children: in 0-6 years - the parents become initially ill (40.7%) or the disease begins simultaneously (32.55%). In school-age children outbreaks in about half of the cases (51.35%) the children manifest the disease the first. There is a tendency of outbreaks percentage increase in the cases where the children, the organized ones as well (from 43% to 62.5%) constitute the primary source of infection.Conclusions. SARS-CoV-2 viral infection epidemiological particularities evaluation in family outbreaks is one of the most important conditions in developing action and response strategies to COVID-19 infection in the community.
Keywords: COVID-19 infection; children; family outbreaks; sources of infection.